2012
DOI: 10.1007/s00445-012-0645-6
|View full text |Cite
|
Sign up to set email alerts
|

Standardisation of the USGS Volcano Alert Level System (VALS): analysis and ramifications

Abstract: warning system (EWS) for all natural hazards and communities. Certainly, the scope of the disaster, with 8 the tsunami causing loss of life in 14 countries, pointed to the need for a readily translatable, easily 9 understood alert system that could be disseminated quickly via diverse communication media. More 10 often, however, standardisation has been the goal and product of nation-state planning; a trend 11 accelerated in post-9/11 United States (U.S.) and Europe as part of the drive toward increased 12 'sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…This was also identified by Thompson et al (2015) in using probabilistic volcanic hazard maps. We found that taking into account the local context is vital, which supports the findings of numerous recent research in volcanic crisis communication (Haynes et al 2007;Fearnley et al 2012;Potter et al 2014). Providing supporting information using other means helps to alleviate these issues.…”
Section: Volcanic Crisis Communicationsupporting
confidence: 87%
“…This was also identified by Thompson et al (2015) in using probabilistic volcanic hazard maps. We found that taking into account the local context is vital, which supports the findings of numerous recent research in volcanic crisis communication (Haynes et al 2007;Fearnley et al 2012;Potter et al 2014). Providing supporting information using other means helps to alleviate these issues.…”
Section: Volcanic Crisis Communicationsupporting
confidence: 87%
“…4A) and levels of detail, with an emphasis on uncertainty. For example, the United States Geological Survey operate dual volcano alert level systems to accommodate both the aviation industry, who require hazard information as rapidly as possible, and those responsible for hazard response on the ground who may prefer a lead time to inform and educate decision makers (Fearnley et al, 2012). While relevant information for long-term infrastructure and public service planning should capture broad changes between years or decades, monitoring data that feeds into decisions about evacuation must be available on much shorter timescales in as near to realtime as possible (Tilling, 2008).…”
Section: Temporal Properties Of Volcanic and Magmatic Insar Signalsmentioning
confidence: 99%
“…Such evaluations are usually expressed in terms of alert levels (e.g., Fearnley et al 2012), represented by a series (usually three to five, but they can be more) of discrete levels, determined by volcano scientists on the basis of their observations and expert knowledge, each one implicitly (or in some cases explicitly) associated with a different "likelihood", which, in turn, is sometimes tied to associated actions. The arguments that I develop here demonstrate that such alert level tables are dominantly developed and used through an 'intuitive approach' , rather than through rational thinking that should drive scientific evaluations.…”
Section: Introductionmentioning
confidence: 99%